(untitled) (Biological Sciences - PJSIR, 2024)
The aim of the study is to use natural sources as antifungal against food born fungi to avoid chemical toxicity on fruits and vegetables. In current study, antifungal property of different vinegars have been evaluated against some fruits born fungi. Fungal isolates were identified by macroscopic and microscopic study. Antifungal activity of three types of vinegars was evaluated by agar well diffusion method. Three types of fungal isolates i.e. Acremonium species, Aspergillus flavus and Fusarium solani isolated form orange, guava and strawberry respectively, were identified using 40x and 100x lenses of microscope. Synthetic white vinegar and mixed fruit vinegar showed maximum activity against Acremonium species forming zone of inhibition of 15±0.05 mm and 12±0.05 mm. Syzygium cumini vinegar showed maximum antifungal activity against A. flavus forming zones of inhibition 10±0.05 mm. Vinegar coatings, sprays or fumes can be better alternate of chemical fungicides to keep fungal pathogens and chemical toxicity away from food.